Comparing The Effectiveness Of Animated And Still Graphic In Multimedia Learning - S.Aloobody, Mohammad (2010)
This study was to determine if there is any difference in the effectiveness of animated graphics with text presentations as compared to still graphics with text presentations in comprehension and recall levels. As the use of multimedia elements in e-content could have different effectiveness, it is worth knowing in details how different combinations of multimedia elements could have different levels of effectiveness. The comparison was between: a computer generated animated graphic with text, and a series of still graphic with text to deliver a process leaning content type.